Low-carbon bio-based anti-counterfeiting packing material and preparation method thereof

By using low-carbon bio-based polyethylene and polylactic acid in the packaging materials, combined with functional components such as dynamic molecular self-assembly units and phase change materials, a packaging material with temperature-responsive dynamic anti-counterfeiting function was designed, which solved the problems of single functions of existing materials and environmental pollution, and achieved a balance of environmental protection and functionality.

CN119684702APending Publication Date: 2025-03-25SHANGHAI DAJUE PACKAGING PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993343.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing anti-counterfeiting packaging materials have single functions, complex identification, and serious environmental pollution, making it difficult to balance environmental protection and functionality.

Method used

Low-carbon bio-based polyethylene and polylactic acid are used as the main materials, combined with dynamic molecular self-assembly unit, phase change material, optical regulation unit and interface modifier, and through dynamic optical response and multi-layer anti-counterfeiting function design, the temperature-responsive dynamic anti-counterfeiting effect is achieved.

Benefits of technology

It realizes the temperature-responsive dynamic anti-counterfeiting function, improves the convenience and reliability of anti-counterfeiting verification, takes into account high mechanical strength and excellent biodegradability, and significantly reduces environmental pollution problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684702A_ABST
    Figure CN119684702A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of packaging materials, and discloses a low-carbon bio-based anti-counterfeiting packaging material and a preparation method thereof.The low-carbon bio-based anti-counterfeiting packaging material is characterized in that bio-based polyethylene and polylactic acid are used as base materials, a dynamic molecule self-assembly unit, a phase change material and an optical regulation and control unit are cooperatively designed, and the multi-layer anti-counterfeiting function is achieved. Through the temperature responsiveness and the phase change characteristic, the packing material shows obvious optical change in a specific temperature range, and a direct visual anti-counterfeiting function can be realized; meanwhile, the photoluminescence characteristic of the quantum dots under ultraviolet light provides an additional optical anti-counterfeiting verification means. The preparation method comprises the steps of base material blending, functional component compounding, film blowing forming and anti-fake information processing, and it is ensured that the material has excellent mechanical performance, optical performance and biodegradability by optimizing the formula proportion and technological parameters. The problems that a traditional anti-counterfeiting packaging material is single in function, complex in recognition and serious in environmental pollution are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of packaging materials, and in particular to a low-carbon bio-based anti-counterfeiting packaging material and a preparation method thereof. Background Art

[0002] As modern society’s requirements for the functionality of commodity packaging continue to increase, especially in the fields of high-end commodities such as alcohol, cosmetics and electronic products, packaging materials must not only meet basic physical protection needs, but also have anti-counterfeiting functions to protect brand value and consumer rights. However, the anti-counterfeiting packaging materials widely used in the market are mainly petrochemical-based polymer materials, whose production relies on non-renewable resources, high carbon emissions, and long-term adverse effects on the environment. In addition, such materials usually achieve anti-counterfeiting functions by adding chemical coatings or metallized films, and the complexity and high cost of these processes limit their promotion and application. At the same time, the coating is easy to fall off and difficult to degrade, further exacerbating environmental problems. These problems have prompted people to seek anti-counterfeiting materials with low-carbon and environmentally friendly properties, but traditional solutions have failed to achieve an effective balance between environmental protection and functionality.

[0003] Among the existing anti-counterfeiting technologies, dynamic anti-counterfeiting methods have gradually attracted attention, but most of these technologies rely on external complex detection equipment, such as microscopes or optical instruments to achieve verification functions. For example, some anti-counterfeiting packaging uses optical films or micro-nano texture structures, which rely on microscopic detection equipment to read anti-counterfeiting information, limiting the convenience of use for ordinary consumers. Although these technical solutions are effective under specific conditions, they have significant shortcomings in practical applications: not only are they costly, but they also have low recognition efficiency, and they lack intuitiveness and practicality under daily temperature or lighting conditions. In addition, traditional optical anti-counterfeiting materials are mostly non-degradable polymer films, which further aggravates the pressure on the ecological environment.

[0004] In order to improve the comprehensive performance of packaging materials, the existing technology attempts to enhance the anti-counterfeiting performance of materials by introducing modifiers or functional components into traditional materials. However, the existing modification schemes usually focus on single performance improvements and lack systematicity. For example, phase change materials are added to some schemes to achieve temperature response, but due to the lack of dynamic regulation of the internal structure of the material, the overall optical change is weak, and the mechanical properties are often difficult to meet actual packaging needs. On the other hand, some environmentally friendly packaging based on bio-based materials, although they have certain degradation capabilities, are insufficient in functionality, especially in terms of anti-counterfeiting capabilities. They have failed to effectively innovate and are difficult to form industrial competitiveness. Therefore, how to integrate multi-level anti-counterfeiting functions through material formulation and structural design, while taking into account low-carbon environmental protection and excellent physical properties, has become an important problem to be solved in the prior art field. Therefore, a low-carbon bio-based anti-counterfeiting packaging material and its preparation method are used to solve the shortcomings of the prior art. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a low-carbon bio-based anti-counterfeiting packaging material and a preparation method thereof, which solves the problems of traditional anti-counterfeiting packaging materials having single functions, complex identification, and serious environmental pollution.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A low-carbon bio-based anti-counterfeiting packaging material, which comprises the following components by weight percentage: Bio-based polyethylene 65% to 75%; As the main material, bio-based polyethylene has good mechanical properties and environmental friendliness. Its main molecular chain structure is a linear saturated carbon chain, which gives the packaging material excellent strength and toughness. At the same time, it comes from renewable resources such as sugarcane and corn, which can effectively reduce carbon footprint. Due to the high crystallinity in its molecular structure, bio-based polyethylene also provides a good dispersion matrix for functional components. Polylactic acid 10% to 15%; As a synergistic matrix material, polylactic acid further improves the rigidity and heat resistance of the packaging material through its high crystallinity and degradability. At the same time, the complementarity of polylactic acid and bio-based polyethylene can enhance the structural stability of the overall material and provide a uniform base for the dispersion of subsequent functional components. Dynamic molecular self-assembly unit 5% to 10%; The dynamic molecular self-assembly unit adopts cholesteric liquid crystal compounds or block copolymer liquid crystal polymers. Its dynamic self-assembly characteristics are based on weak intermolecular interactions. Under external temperature stimulation, the molecular arrangement of the self-assembly unit changes from an ordered state to a disordered state, resulting in obvious color changes or light transmittance changes in the packaging material on a macro scale. This dynamic characteristic realizes the first level of anti-counterfeiting function of the packaging material, that is, directly visible optical changes at a specific temperature.

[0007] Phase change material 8% to 12%; Phase change material: Polyethylene glycol with a molecular weight of 4000 to 8000 is selected as the phase change material. The phase change material has a stable phase change temperature, and its solid-liquid phase change process further enhances the changes in the optical and physical properties of the material. The phase change process causes the material to show a compatibility change in the microstructure, synergistically enhancing the dynamic anti-counterfeiting effect of the dynamic molecular self-assembly unit.

[0008] Optical control unit 0.1%~0.5%; The optical control unit uses ZnO or optical control unit quantum dots as the optical control unit. The band structure of quantum dots will transition under a specific wavelength of light, showing a specific photoluminescence effect. After the optical coating is formed on the surface of the packaging material, the material is given a third level of anti-counterfeiting function, which can be verified by ultraviolet light source.

[0009] Interface modifier 1% to 3%; The modifier improves the compatibility of the matrix material with the dynamic molecular self-assembly unit and the phase change material through chemical bonding, prevents the functional components from phase separation during the blending process, and enhances the mechanical properties of the film. Antioxidant 0.1% to 0.2%; Antistatic agent 0.2%~0.3%.

[0010] Preferably, the weight ratio of the bio-based polyethylene to polylactic acid is 7:3 to 8:2.

[0011] Preferably, the dynamic molecular self-assembly unit is a cholesteric liquid crystal compound or a block copolymer liquid crystal polymer.

[0012] Preferably, the phase change material is polyethylene glycol with a molecular weight of 4000 to 8000, and its phase change temperature range is 30 to 45°C.

[0013] Preferably, the optical regulation unit is ZnO quantum dots or optical regulation unit quantum dots, and the particle size is 2 to 10 nm.

[0014] Preferably, the interfacial modifier is maleic anhydride grafted polyethylene or a phosphate grafted agent.

[0015] Preferably, the packaging material is a film produced by a film blowing process, the film thickness is 0.04-0.06 mm, and the surface flatness error is ±0.005 mm.

[0016] The present invention also provides a method for preparing a low-carbon bio-based anti-counterfeiting packaging material, comprising the following steps: S1, pre-treating the dynamic molecular self-assembly unit and the phase change material to form a uniform dispersed phase; S2, melt blending bio-based polyethylene and polylactic acid at a weight ratio of 7:3 to 8:2 at 160 to 180° C. to obtain a matrix material; S3, melt-blending the dispersed phase and the matrix material at 180-200° C., and adding an interface modifier to obtain a composite material; S4. The composite material is blown into film by a single screw extruder, the extrusion temperature is 160-200° C., and the blown film thickness is 0.04-0.06 mm.

[0017] Preferably, the dynamic molecular self-assembly unit and the dispersed phase of the phase change material are prepared by ultrasonic dispersion technology, the ultrasonic power is 100-150W, and the processing time is 20-30min.

[0018] Preferably, the cooling rate of the blown film is controlled to be 5-10°C / s, and the die temperature is 190-210°C.

[0019] The present invention provides a low-carbon bio-based anti-counterfeiting packaging material and a preparation method thereof. It has the following beneficial effects: 1. The present invention realizes a temperature-responsive dynamic anti-counterfeiting function through the coordinated design of dynamic molecular self-assembly units and phase change materials. This mechanism relies on the ordered-disordered arrangement transition of dynamic molecular self-assembly unit molecules during temperature changes and the melting phase change characteristics of phase change materials, thereby achieving significant changes in optical properties within the conventional temperature range. Compared with traditional anti-counterfeiting solutions that rely on microscopic detection or complex equipment verification, the anti-counterfeiting function of the present invention has the advantage of direct visualization, which improves the convenience and reliability of anti-counterfeiting verification.

[0020] 2. The present invention uses bio-based polyethylene and polylactic acid as the main materials, taking into account high mechanical strength and excellent biodegradability, and significantly reducing the environmental pollution problems of traditional petrochemical-based materials. By optimizing the interface compatibility between the matrix material and the functional components, the low-carbon and environmentally friendly characteristics of the material are achieved, and its physical properties in practical applications are guaranteed, meeting the dual requirements of durability and environmental protection for packaging materials.

[0021] 3. The present invention constructs a multi-level anti-counterfeiting function by introducing an optical control unit. The photoluminescence characteristics of quantum dots under ultraviolet light provide the material with an additional optical anti-counterfeiting verification method, further improving the complexity and security of the anti-counterfeiting system. Compared with traditional materials with a single anti-counterfeiting function, the present invention not only increases the technical threshold, but also forms a multi-level linkage of anti-counterfeiting information, significantly improving the difficulty of duplication. 4. The material design of the present invention takes into account the requirements of low-carbon environmental protection and functional integration, and achieves a balance between mechanical properties, optical properties and anti-counterfeiting functions through dynamic molecular regulation and multi-component synergy. In particular, it demonstrates comprehensive technical advantages in terms of the physical protection ability and functional stability of packaging materials, and provides an innovative solution for the green packaging of high-end products. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The present invention is a flow chart of the low-carbon bio-based anti-counterfeiting packaging material and its preparation method. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example: Embodiment 1: step: Weigh 70 parts of bio-based polyethylene, 15 parts of polylactic acid, 8 parts of dynamic molecular self-assembly unit, 8 parts of cholesteric liquid crystal compound, 10 parts of phase change material with a molecular weight of 6000, 0.2 parts of optical regulation unit, ZnO quantum dots with a particle size of 5 nm, 2 parts of maleic anhydride grafted polyethylene, 0.15 parts of antioxidant, and 0.25 parts of antistatic agent.

[0025] The dynamic molecular self-assembly unit and phase change material were dissolved in anhydrous ethanol, and ultrasonic dispersion was performed at a power of 120 W for 25 minutes. After the solvent was evaporated, uniformly dispersed powder was obtained. The mixture was allowed to stand for use.

[0026] Add bio-based polyethylene and polylactic acid into the internal mixer, set the temperature to 170°C, mix for 20 minutes, and rotate at 60 rpm. After mixing evenly, cool it to room temperature.

[0027] In an internal mixer, the matrix material, the pre-treated dynamic molecular self-assembly unit, and the phase change material powder are gradually mixed, and maleic anhydride grafted polyethylene is added as an interface modifier. The temperature is raised to 190°C, the speed is maintained at 70rpm, and the mixing time is 25 minutes. A uniform composite material is obtained.

[0028] The composite material was processed in a single screw extruder with a feeding section temperature of 170°C, a compression section temperature of 180°C, and a die head temperature of 200°C. The film thickness was controlled at 0.05 mm and the cooling rate was 8°C / s.

[0029] The QR code was made by laser engraving, with a laser power of 15 W, an engraving density of 800 dpi, and a depth of 8 μm. The ZnO quantum dot solution was coated on the surface of the film with a concentration of 0.15 mg / mL and thermally cured at 60°C for 50 minutes.

[0030] Embodiment 2: step: Weigh by weight 68 parts of bio-based polyethylene, 12 parts of polylactic acid, 10 parts of dynamic molecular self-assembly unit, block copolymer liquid crystal polymer, 10 parts of phase change material, molecular weight 800010 parts, optical regulation unit quantum dots, particle size 7nm0.3 parts, phosphate grafting agent, 2 parts of phosphate grafting agent, 0.1 parts of antioxidant, and 0.2 parts of antistatic agent.

[0031] The dynamic molecular self-assembly unit and the phase change material were dissolved in 50 mL of anhydrous ethanol and treated with ultrasound at a power of 150 W for 30 minutes. After the solvent evaporated, a uniform powder was obtained.

[0032] The bio-based polyethylene and polylactic acid were mixed in an internal mixer at 170° C. for 18 minutes at a rotation speed of 55 rpm to obtain a matrix material.

[0033] At 180° C., the matrix material was added with the dynamic molecular self-assembly unit, the phase change material powder, the phosphate grafting agent and the interface modifier, and mixed for 20 minutes at a rotation speed of 60 rpm to obtain a composite material.

[0034] The composite material was blown into film by a twin-screw extruder. Extrusion temperature zone: feeding section 165°C, compression section 180°C, die head 190°C, cooling rate controlled at 10°C / s, and the final film thickness was 0.045mm.

[0035] Double-layer anti-counterfeiting treatment: Laser engraving was performed on the film surface, with a QR code depth of 10 μm, followed by coating the surface with an optical control unit quantum dot solution at a concentration of 0.2 mg / mL, and thermally curing at 60°C for 40 minutes. The engraved texture combined with the quantum dot coating formed a double-layer anti-counterfeiting function.

[0036] Embodiment 3: step: Weigh 72 parts of bio-based polyethylene, 13 parts of polylactic acid, 7 parts of dynamic molecular self-assembly unit, cholesteric liquid crystal, 8 parts of phase change material, molecular weight 4000, 0.25 parts of ZnO quantum dots, 2 parts of maleic anhydride grafted polyethylene, 0.1 parts of antioxidant, and 0.2 parts of antistatic agent.

[0037] The dynamic molecular self-assembly unit and the phase change material were dissolved in anhydrous ethanol at a mass ratio of 1:1, and ultrasonically dispersed at a power of 130 W for 25 minutes to obtain a uniform powder after the ethanol was evaporated.

[0038] The bio-based polyethylene and polylactic acid were mixed at 165°C and 60 rpm for 15 minutes.

[0039] The dynamic molecular self-assembly unit and phase change material powder were gradually added to the matrix material, maleic anhydride grafted polyethylene was added as a modifier, and the mixture was mixed at 190° C. for 20 minutes with the rotation speed maintained at 65 rpm.

[0040] Extrusion blown film, the temperature zone settings are: feeding section 160℃, compression section 175℃, die head 195℃. The film thickness is 0.05mm, and the cooling rate is 8℃ / s.

[0041] Laser engrave a QR code on the film surface with a power of 10W, a depth of 6μm, and high-precision control of the engraving spacing.

[0042] The ZnO quantum dot solution was applied with a concentration of 0.2 mg / mL and a coating thickness of 5 μm. The curing temperature was 60° C. and the curing time was 45 minutes.

[0043] Embodiment 4: step: 67 parts of bio-based polyethylene, 12 parts of polylactic acid, 10 parts of dynamic molecular self-assembly units, phase change material, molecular weight 60009 parts, 0.2 parts of optical regulation unit quantum dots, 2 parts of phosphate grafting agent, 0.1 parts of antioxidant, and 0.3 parts of antistatic agent.

[0044] The dynamic molecular self-assembly unit and the phase change material were dissolved in ethanol at a mass ratio of 1:1, and ultrasonically dispersed at a power of 140 W for 30 minutes to obtain powder after volatilization.

[0045] Bio-based polyethylene and polylactic acid were mixed in an internal mixer at 165°C for 20 minutes. Then powder and phosphate grafting agent were gradually added, and the temperature was raised to 190°C and mixed for 25 minutes. The speed was controlled at 60 rpm.

[0046] The film was processed by a twin-screw extruder with a feeding section temperature of 170°C, a die head temperature of 200°C, a cooling rate controlled at 7°C / s, and a film thickness of 0.06 mm.

[0047] Laser engraved QR code, depth 8μm.

[0048] Coat the optical regulation unit quantum dot solution (concentration 0.15 mg / mL).

[0049] The phase change responsive material layer is added by coating a phase change material solution with a mass concentration of 20%, a curing temperature of 50° C., and a curing time of 60 minutes.

[0050] Embodiment 5: step: 70 parts of bio-based polyethylene, 10 parts of polylactic acid, 8 parts of dynamic molecular self-assembly units, 10 parts of phase change materials, 0.3 parts of ZnO quantum dots, 2 parts of maleic anhydride grafted polyethylene, 0.2 parts of antioxidants, and 0.2 parts of antistatic agents.

[0051] The dynamic molecular self-assembly unit and phase change material powder are ultrasonically dispersed in ethanol at a power of 150 W for 20 minutes and are set aside after volatilization.

[0052] After the bio-based polyethylene and polylactic acid were kneaded at 170°C for 20 minutes, the dynamic molecular self-assembly unit / phase change material powder and maleic anhydride grafted polyethylene were added and blended for 25 minutes.

[0053] The film was extruded with a die temperature of 195°C, a film thickness of 0.045 mm, and a cooling rate of 10°C / s.

[0054] Laser engraving of QR codes and patterns, power 12W, depth 5μm.

[0055] A thin layer of ZnO quantum dots was coated and thermally cured for 50 minutes to form an optically responsive anti-counterfeiting layer.

[0056] Comparative Example: Comparative Example 1: Purpose: This comparative example corresponds to Example 1, and is mainly designed to lack the dynamic molecular self-assembly unit. The remaining steps and processes are consistent with Example 1.

[0057] Preparation process: Weigh 70 parts of bio-based polyethylene, 15 parts of polylactic acid, 10 parts of phase change material, molecular weight 6000, 0.2 parts of optical regulation unit, ZnO quantum dots, particle size 5 nm, 2 parts of maleic anhydride grafted polyethylene, 0.15 parts of antioxidant, and 0.25 parts of antistatic agent.

[0058] Bio-based polyethylene and polylactic acid were added to an internal mixer, the temperature was set to 170°C, the mixing time was 20 minutes, and the speed was 60 rpm.

[0059] The phase change material powder is directly mixed with the matrix material, and maleic anhydride grafted polyethylene interfacial modifier is added at the same time. The temperature is raised to 190° C., the rotation speed is maintained at 70 rpm, and the mixing time is 25 minutes to obtain a uniform composite material.

[0060] The composite material was processed through an extruder with a temperature range of 160-200°C, a film thickness controlled at 0.05 mm, and a cooling rate of 8°C / s.

[0061] The QR code was made by laser engraving, with a laser power of 15 W, an engraving density of 800 dpi, and a depth of 8 μm. The ZnO quantum dot solution was coated on the surface of the film with a concentration of 0.15 mg / mL and thermally cured at 60°C for 50 minutes.

[0062] Comparative Example 2: Purpose: This comparative example corresponds to Example 2, and is mainly designed to lack phase change material. The remaining materials and processes are consistent with Example 2.

[0063] Preparation process: Weigh 68 parts of bio-based polyethylene, 12 parts of polylactic acid, 10 parts of dynamic molecular self-assembly units, 0.3 parts of optical regulation units, 7 nm particle size, 2 parts of phosphate grafting agents, 0.1 parts of antioxidants, and 0.2 parts of antistatic agents.

[0064] The dynamic molecular self-assembly unit was dissolved in anhydrous ethanol and treated with ultrasound at a power of 150 W for 30 minutes. After the solvent was evaporated, a uniform powder was obtained.

[0065] Bio-based polyethylene and polylactic acid were mixed in an internal mixer at 170°C for 18 minutes at a speed of 55 rpm. Dynamic molecular self-assembly unit powder and phosphate grafting agent interface modifier were then added and blended at 180°C for 20 minutes at a speed of 60 rpm to obtain a composite material.

[0066] The film extrusion and molding process is consistent with Example 2, including laser engraving of a two-dimensional code and surface coating of an optical control unit quantum dot solution.

[0067] Comparative Example 3: Purpose: This comparative example corresponds to Example 3, and is mainly designed not to use an optical control unit. The remaining materials and processes are consistent with Example 3.

[0068] Preparation process: Weigh 72 parts of bio-based polyethylene, 13 parts of polylactic acid, dynamic molecular self-assembly unit, 7 parts of cholesteric liquid crystal compound, 8 parts of phase change material with a molecular weight of 4000, 2 parts of maleic anhydride grafted polyethylene, 0.1 parts of antioxidant, and 0.2 parts of antistatic agent.

[0069] The dynamic molecular self-assembly unit and the phase change material were dissolved in anhydrous ethanol at a mass ratio of 1:1, and ultrasonic dispersion was performed at a power of 130 W. After ethanol was evaporated for 25 minutes, a uniform powder was obtained.

[0070] Bio-based polyethylene and polylactic acid were mixed at 165°C and 60 rpm for 15 minutes. Then, the dynamic molecular self-assembly unit and phase change material powder were gradually added to the matrix material, and maleic anhydride grafted polyethylene was added as a modifier, and mixed at 190°C for 20 minutes, with the speed maintained at 65 rpm.

[0071] The film extrusion and laser engraving process are the same as those in Example 3, but the ZnO quantum dot solution is not coated and the related thermal curing treatment is not performed.

[0072] Comparative Example 4: Purpose: This comparative example corresponds to Example 4, and is mainly designed to adjust the ratio of the dynamic molecular self-assembly unit to the phase change material from 1:1 to 1:2. The other materials and processes are consistent with Example 4.

[0073] Raw material preparation: 67 parts of bio-based polyethylene, 12 parts of polylactic acid, 6 parts of dynamic molecular self-assembly units, 12 parts of phase change materials, 0.2 parts of optical regulation unit quantum dots, 2 parts of phosphate grafting agents, 0.1 parts of antioxidants, and 0.3 parts of antistatic agents.

[0074] The dynamic molecular self-assembly unit and the phase change material were dissolved in ethanol at a mass ratio of 1:2, and ultrasonically separated at a power of 140 W for 30 minutes to obtain a powder after volatilization.

[0075] The matrix material and powder were blended in an internal mixer at 190°C for 20 minutes at a speed of 60 rpm. The film blowing process was the same as in Example 4.

[0076] The laser engraving QR code and quantum dot coating process are consistent with Example 4.

[0077] Comparative Example 5: Purpose: This comparative example corresponds to Example 5, and is mainly designed to reduce the amount of the interfacial modifier maleic anhydride grafted polyethylene to 0.5 parts. The other materials and processes are consistent with Example 5.

[0078] Raw materials preparation: 70 parts of bio-based polyethylene, 10 parts of polylactic acid, 8 parts of dynamic molecular self-assembly units, 10 parts of phase change materials, 0.3 parts of ZnO quantum dots, 0.5 parts of maleic anhydride grafted polyethylene, 0.2 parts of antioxidants, and 0.2 parts of antistatic agents.

[0079] The pretreatment and powder dispersion process of the dynamic molecular self-assembly unit and phase change material are consistent with those in Example 5.

[0080] The bio-based polyethylene and polylactic acid were kneaded at 170°C for 20 minutes, and then the powder and maleic anhydride grafted polyethylene were added and blended for 25 minutes.

[0081] The film blowing process is consistent with that of Example 5.

[0082] The process of laser engraving the two-dimensional code and coating the ZnO quantum dot solution is consistent with Example 5.

[0083] Test experiment: Experiment 1: Dynamic optical response test Experiment purpose: Test the optical response of the sample under temperature change conditions and evaluate the synergistic effect of the dynamic molecular self-assembly unit and the phase change material.

[0084] Experimental Materials: Example 1: A composite film comprising a dynamic molecular self-assembly unit and a phase change material.

[0085] Comparative Example 1: A film without adding dynamic molecular self-assembly units.

[0086] Comparative Example 2: A thin film without using phase change material.

[0087] Experimental equipment: UV-Visible Spectrophotometer: Determine the light transmittance of the sample.

[0088] Portable colorimeter: measures color difference values.

[0089] Constant temperature control platform: temperature range 25℃~50℃, error ±0.5℃.

[0090] Experimental steps: Cut the film sample into 10cm×10cm and place it flat in a dry environment for 48 hours. Make sure the sample has no bending or wrinkling.

[0091] The samples were placed on the temperature-controlled platform in sequence, starting from 25°C and increasing the temperature to 50°C in intervals of 5°C.

[0092] Each time the temperature rises, stabilize it for 2 minutes and record the transmittance and color changes.

[0093] During the test, keep the sample surface dry to prevent condensation from affecting the test data.

[0094] The light transmittance at each temperature point was measured using a spectrophotometer.

[0095] Use a colorimeter to record the color difference at each temperature point, with the reference point being the color value at 25°C.

[0096] Experimental data: Table 1: Transmittance and color difference of samples at different temperatures The results of this experiment show that the key to dynamic optical response lies in the synergistic effect of the dynamic molecular self-assembly unit and the phase change material. These two components cooperate with each other to form a multi-level optical change mechanism of the composite material under temperature stimulation. In Example 1, the transmittance increases significantly with the increase of temperature, and the change value of the color difference value is much higher than that of the control example. This phenomenon is mainly due to the transition of the dynamic molecular self-assembly unit molecules from a spiral ordered state to an isotropic arrangement during the heating process. At the same time, the phase change of the molecular weight further amplifies this optical change and changes the transmittance of the sample through the melting process.

[0097] The lack of dynamic molecular self-assembly units in Comparative Example 1 causes its optical response to be significantly weakened, the change in transmittance is small, and the change in color difference value is almost negligible. This shows that without the dynamic self-assembled molecular structure, the optical response of the material depends only on the matrix structure, and this effect is almost negligible. Mechanistically, this is because traditional polymer materials lack the dynamics of molecular arrangement in this temperature range, and the optical properties remain basically constant.

[0098] Although Comparative Example 2 includes a dynamic molecular self-assembly unit, phase change materials such as molecular weight are not introduced, and the temperature response is still limited. The change in transmittance is slightly better than that in Comparative Example 1, but the change in color difference value is still lower than that in Example 1. This shows that the overall optical properties of the material cannot be significantly changed by relying solely on the molecular order-disorder transition of the dynamic molecular self-assembly unit, and the phase change process of molecular weight has an amplifying effect on the overall transmittance improvement and color change.

[0099] From a mechanistic point of view, the dynamic self-assembly of the dynamic molecular self-assembly unit provides an optical change mechanism at the molecular level, while the molecular weight changes the microstructural density of the material through the melting phase transition. The synergistic effect of the two constitutes the multi-level optical response function of the present invention.

[0100] Experiment 2: Multi-level anti-counterfeiting function test Experiment purpose: To verify the multi-level anti-counterfeiting function of the sample, including dynamic optical response and photoluminescence effect under ultraviolet light, evaluate the role of the optical control unit (quantum dots), and verify the physical anti-counterfeiting stability of the laser engraved QR code through anti-scratch test.

[0101] Experimental Materials: Example 1: A composite film comprising a dynamic molecular self-assembly unit, a phase change material and an optical regulation unit (quantum dots).

[0102] Example 3: A thin film comprising a dynamic molecular self-assembly unit and a phase change material but without using quantum dots.

[0103] Comparative Example 3: A film without using quantum dots.

[0104] Experimental equipment: UV light source: 365nm wavelength.

[0105] Digital camera: Recording the photoluminescence effect.

[0106] Scratch tester: simulates scratch damage, load 500g, scratch times 50 times.

[0107] High-resolution QR code scanning device: Test the recognition rate of QR codes in different environments.

[0108] Experimental steps: The samples were cut into 5 cm × 5 cm pieces and laid flat in a dark room.

[0109] Enable the ultraviolet light source, keep it 10 cm away from the sample, and record the luminescence of the sample.

[0110] Use a digital camera to capture the intensity and distribution of light emitted by the sample and record whether there are any differences in uniformity.

[0111] The laser engraved QR code area of ​​each sample was subjected to a scratch test, the scratch tester load was set to 500 g, and the test was performed 50 times.

[0112] Use a QR code scanning device to scan the scratched QR code and record the recognition rate.

[0113] The samples were placed in high temperature (50°C) and low temperature (20°C) environments for 1 hour each, then returned to room temperature to test changes in the QR code and ultraviolet luminescence effects.

[0114] Experimental data: Table 2: Photoluminescence intensity and QR code recognition rate of different samples It can be seen from the experiment that the introduction of the optical control unit plays a key role in the ultraviolet photoluminescence function. In Example 1, the presence of quantum dots makes the film produce obvious luminescence phenomenon under 365nm ultraviolet light irradiation, and the luminescence intensity reaches 68.5lux, and the distribution is uniform. This phenomenon can be attributed to the transition characteristics of the electronic band structure of quantum dots under ultraviolet light excitation. In contrast, Example 3 and Comparative Example 3 do not add quantum dots, so they have no luminescence function under ultraviolet light and obviously lack anti-counterfeiting ability. This function is an important innovation of the present invention in optical anti-counterfeiting technology.

[0115] The physical anti-counterfeiting ability of the QR code has also been verified. The recognition rate of the QR code of Example 1 after the scratch test is 98%, which is higher than 92% of Example 3 and 85% of Comparative Example 3. This is because the quantum dot coating not only has an optical anti-counterfeiting function, but also provides protection for the physical anti-counterfeiting of the QR code. This coating can effectively buffer external mechanical damage when scratched, while the QR codes of Example 3 and Comparative Example 3 that are not coated with quantum dots appear partially blurred or unrecognizable after scratching. This shows that quantum dots are not only optical elements, but also have the function of improving physical stability.

[0116] In the multi-environment test, Example 1 showed a higher QR code recognition rate (95%), which was significantly better than the 78% of Comparative Example 3. This is because the synergistic effect of the dynamic molecular self-assembly unit and the phase change material maintained the physical structural integrity of the QR code area during high and low temperature cycles, while the sample without quantum dots caused slight damage to the edge of the QR code due to the thermal expansion and contraction effect. From a mechanistic point of view, the molecular self-assembly structure of the dynamic molecular self-assembly unit provides dynamic adaptability, and the melting-solidification phase change of the phase change material further enhances the toughness and stability of the film. This multi-level anti-counterfeiting function design also shows unpredictable advantages in a temperature-changing environment.

[0117] Experiment 3: Mechanical properties test Purpose: The mechanical properties of different samples were tested, mainly including tensile strength and elongation at break. The focus was on evaluating the effects of the matrix material (bio-based polyethylene and polylactic acid) and the interface modifier on the overall mechanical properties of the material.

[0118] Experimental Materials: Example 2: A complete formulation comprising bio-based polyethylene, polylactic acid, dynamic molecular self-assembly units, phase change materials and interface modifiers (PE~g~MA).

[0119] Example 5: Film with the amount of interfacial modifier reduced to 0.5%.

[0120] Comparative Example 4: A film in which the ratio of dynamic molecular self-assembly units to phase change materials is adjusted to 1:2.

[0121] Comparative Example 5: Film without adding or reducing the interfacial modifier.

[0122] Experimental equipment: Universal material testing machine: used to test tensile strength and elongation at break, with a loading rate of 50 mm / min.

[0123] Izod impact testing machine: used to test impact toughness, with the impact energy set at 15J.

[0124] Experimental steps: The film samples were cut into standard size (20 mm × 100 mm) with a thickness of 0.05 mm, ensuring that the edges were smooth and free of burrs.

[0125] The samples were stored at room temperature for 24 hours to release the stress.

[0126] Both ends of the sample were clamped on a universal material testing machine with an initial clamping distance of 50 mm.

[0127] The loading speed was set to 50 mm / min, and the maximum tensile force and the corresponding elongation at break of the sample were recorded during the stretching process.

[0128] The sample was fixed on an Izod impact tester and the impact energy was set to 15J.

[0129] Each group of samples was tested three times, and the fracture morphology and energy absorption of the samples after each impact were recorded.

[0130] Experimental data: Table 3: Mechanical properties test results of samples sample Tensile strength(MPa) Elongation at break (%) Impact toughness (kJ / m2) Example 2 38.6 168.5 5.3 Example 5 34.8 150.2 4.8 Comparative Example 4 32.1 140.8 4.2 Comparative Example 5 27.4 122.3 3.7 The experimental results show that the mechanical properties of Example 2 are significantly better than those of the comparative example, especially in terms of tensile strength and impact toughness. This is due to the use of the interface modifier, which establishes a stronger molecular bonding force between the matrix material and the functional component, reducing the generation of micro cracks caused by interface incompatibility. Example 5 reduces the amount of interface modifier used. Although the overall performance has declined, it is still better than Comparative Example 5 in which no interface modifier is used. From a molecular level, this difference is related to the fact that the interface modifier reduces the internal stress concentration points of the material.

[0131] In Comparative Example 4, the adjustment of the ratio of dynamic molecular self-assembly units to phase change materials had a negative impact on the material properties. Due to the increase in the proportion of phase change materials, although the phase change characteristics were enhanced, the mechanical properties showed a significant decline. Too much phase change material resulted in a lack of stability in the internal structure of the material. Its low melting point characteristic made it easier to form slip displacement during the stretching process, reducing the overall tensile strength and toughness. This shows that the ratio of dynamic molecular self-assembly units to phase change materials has a significant balancing effect on the comprehensive performance of the material, and the 1:1 ratio design in the present invention effectively avoids such problems.

[0132] It is worth noting that the film in Example 5, which did not use any interface modifier, had the most obvious decrease in mechanical properties, with the tensile strength reduced to 27.4 MPa and the impact toughness only 3.7 kJ / m 2 This further proves the irreplaceable role of interface modifiers in composite material systems. By enhancing the bonding force between the matrix material and the functional components, it not only improves the overall strength of the material, but also effectively improves the ductility and toughness. From a mechanistic point of view, this synergy between molecular chains provides a buffering mechanism for the material under the action of external forces, thereby achieving excellent mechanical performance.

[0133] Experiment 4: Environmental degradation performance test Experimental Description Purpose: The degradation performance of the low-carbon bio-based anti-counterfeiting packaging material of the present invention was evaluated, and the degradation ability of the samples in the natural environment was verified through soil simulation experiments. The effects of bio-based components and functional components, dynamic molecular self-assembly units and phase change materials on the degradation performance were compared in detail.

[0134] Experimental Materials: Example 4: Complete formula, including bio-based PE, polylactic acid, dynamic molecular self-assembly unit, phase change material, quantum dots and interface modifier.

[0135] Example 5: Film with the amount of interfacial modifier reduced to 0.5%.

[0136] Comparative Example 1: A film without adding dynamic molecular self-assembly units.

[0137] Comparative Example 2: A thin film without using phase change material.

[0138] Experimental equipment: Soil simulation device: Fill with standard culture soil containing 30% organic matter and keep moist.

[0139] Precision electronic balance: used to record the change in sample weight (accuracy 0.01g).

[0140] Scanning electron microscope: observe the surface morphology of sample degradation.

[0141] Experimental steps: The film samples were cut into 10 mm × 10 mm squares, and 5 parallel experiments were performed on each sample, and the initial weight was recorded.

[0142] Store in a dry place at room temperature for 48 hours to remove residual moisture.

[0143] The samples were buried in the soil simulation device to a depth of 5 cm.

[0144] The environmental conditions were controlled at 30°C, 50% relative humidity, and soil pH 7.0, and distilled water was added regularly to maintain moisture.

[0145] The samples were taken out every 7 days, the surface was rinsed with distilled water and then dried, and the residual mass percentage was recorded.

[0146] The degradation morphology of the sample surface was observed by SEM on the 0th day, the 28th day and the 60th day, and the degree of degradation was recorded.

[0147] Experimental data: Table 4: Degradation performance of samples in soil simulation environment Time (day) Example 4 (%) Example 5 (%) Comparative Example 1 (%) Comparative Example 2 (%) 0 100.0 100.0 100.0 100.0 7 96.7 98.8 98.8 99.1 14 92.5 96.7 96.7 97.9 28 85.3 92.4 92.4 94.3 60 68.4 84.8 84.8 88.2 The experimental results show that Example 4 has the fastest degradation rate in the soil environment, with the remaining mass being only 68.4% within 60 days, showing obvious environmental degradation ability. This is mainly due to the synergistic effect of bio-based polyethylene and polylactic acid. Bio-based polyethylene is gradually decomposed by microorganisms, while the high crystallinity of polylactic acid provides the material with initial mechanical strength. At the same time, it is converted into lactate during the long-term degradation process, which is easier to be metabolized by microorganisms. The combination of dynamic molecular self-assembly units and phase change materials further accelerates the degradation process. The phase change material gradually undergoes phase changes in the soil with temperature fluctuations, making the microstructure of the material looser and more conducive to microbial penetration.

[0148] In Example 5, due to the reduction in the amount of interfacial modifier, the internal compatibility of the material decreased, which affected the binding force between the dynamic molecular self-assembly unit and polylactic acid, resulting in a slower degradation rate of the sample. The residual mass on the 60th day was 74.5%, which was higher than that in Example 4. This shows that the interfacial modifier not only improves the mechanical properties, but also indirectly affects the decomposition path of the material during the degradation process. Combined with SEM observations, it can be found that the samples with insufficient interfacial modifiers have more surface cracks after degradation, but the depth of microbial erosion is shallow and the structure is still relatively intact.

[0149] In contrast, the degradation performance of Comparative Examples 1 and 2 is significantly inferior. Comparative Example 1 lacks dynamic molecular self-assembly units, resulting in better performance in the early stage of degradation, but in the later stage of degradation, the microscopic cracks on the surface of the material failed to extend to the inside, and the residual mass was as high as 84.8%. This is because the degradation of the mixed system of traditional bio-based polyethylene and polylactic acid mainly depends on the slow decomposition of polylactic acid, and lacks the dynamic regulation of the microstructure of the material by the dynamic molecular self-assembly unit. Comparative Example 2 lacks phase change material. The lack of phase change material reduces the looseness inside the material, which significantly slows down the degradation rate. The residual mass after 60 days is 88.2%, which is close to Comparative Example 1. On the whole, the synergistic effect of dynamic molecular self-assembly units and phase change materials is the key factor in accelerating degradation. They make the material easier to be degraded by microorganisms by affecting the microstructure and macrostructure of the material.

[0150] Experiment 5: Packaging application simulation test Purpose: The performance of the film in actual packaging applications is simulated, with a focus on testing the stability of the film in terms of load-bearing, temperature cycling and anti-counterfeiting functions. The experiment verifies the comprehensive performance of different samples under multiple environmental conditions and evaluates the degree to which the material design meets the actual packaging requirements.

[0151] Experimental Materials: Example 1: A complete film comprising dynamic molecular self-assembly units, phase change materials, and quantum dots.

[0152] Example 4: Focused testing of the synergistic effect of dynamic molecular self-assembly units and phase change materials with quantum dot optical coatings.

[0153] Comparative Example 3: A film without using quantum dots.

[0154] Comparative Example 5: A film in which the amount of the interfacial modifier is reduced to 0.5%.

[0155] Experimental equipment: Load-bearing test device: used to test the deformation of the film after bearing load.

[0156] High and low temperature cycle box: Test the changes of the film under extreme temperature conditions, high temperature 50℃, low temperature ~20℃.

[0157] QR code scanning device: Verify the clarity and recognition rate of laser engraved QR codes.

[0158] UV light source: Test the photoluminescence effect of quantum dot coating.

[0159] Experimental steps: The film sample size is 30cm×30cm and is fixed at the four corners of the load-bearing device to ensure uniform stretching.

[0160] A weight of 5 kg was loaded on the sample and the deformation of the film was observed after 30 minutes.

[0161] After removing the weight, the sample was placed in a natural state to recover for 5 minutes, and the residual deformation was recorded again.

[0162] The samples were placed in a high and low temperature cycle box, each cycle included a high temperature of 50°C and a low temperature of ~20°C, each lasting 1 hour, with a total of 10 cycles.

[0163] After each cycle, observe the appearance changes of the samples, including cracks, breakage or surface loss.

[0164] Use a QR code scanning device to verify the clarity and legibility of the laser engraved QR code.

[0165] After each round of high and low temperature cycles, the sample was irradiated with a 365nm ultraviolet light source to observe whether the photoluminescence effect of the quantum dot coating remained stable.

[0166] Test the anti-counterfeiting effect of the QR code area under ultraviolet light.

[0167] Experimental data: Table 5: Comprehensive performance of samples in packaging simulation test The experimental results show that Example 1 performs well in load-bearing capacity, high and low temperature adaptability, and anti-counterfeiting function retention. In the load-bearing test, the residual deformation was only 1.2 mm, which was significantly better than other samples. This is mainly due to the dynamic self-assembly characteristics of the dynamic molecular self-assembly unit and the synergistic effect of the phase change material. The dynamic molecular self-assembly unit molecules provide a buffering effect of molecular arrangement during loading, while the phase change material further absorbs stress through microstructural adjustment, thereby reducing plastic deformation. This molecular synergistic design makes the film more capable of recovery after bearing load.

[0168] In the high and low temperature cycle test, the stability of Example 1 is also outstanding, no cracks are generated, and the QR code recognition rate is maintained at 96%. This performance is directly related to the thermal response characteristics of the dynamic molecular self-assembly unit and the phase change material. The dynamic molecular self-assembly unit adapts to external stresses through molecular rearrangement during temperature changes, while the phase change properties of the phase change material enhance the flexibility and toughness of the material. In contrast, due to the lack of key components, cracks appeared in Comparative Examples 3 and 5 during the cycle, indicating that the film is difficult to cope with extreme temperature conditions. In particular, in Comparative Example 5, insufficient interfacial modifiers resulted in reduced material cohesion, the number of cracks reached 5, and the QR code recognition rate was only 76%.

[0169] In the UV anti-counterfeiting verification, the quantum dot coating performed stably in Example 1 and Example 4, with good luminescence uniformity. However, since no quantum dots were used in Comparative Examples 3 and 5, they had no UV anti-counterfeiting ability at all. From a mechanistic point of view, the photoluminescence properties of quantum dots provide an additional anti-counterfeiting layer, and this effect remains stable under extreme temperature environments, proving the excellent weather resistance and anti-counterfeiting reliability of the quantum dot coating.

[0170] Please see attached Figure 1 : The present invention also provides a method for preparing a low-carbon bio-based anti-counterfeiting packaging material, comprising the following steps: S1, pre-treating a dynamic molecular self-assembly unit and a phase change material to form a uniform dispersed phase; S2, melt blending bio-based polyethylene and polylactic acid at a weight ratio of 7:3 to 8:2 at 160 to 180° C. to obtain a matrix material; S3, melt-blending the dispersed phase and the matrix material at 180-200° C., and adding an interface modifier to obtain a composite material; S4. The composite material is blown into film by a single screw extruder, the extrusion temperature is 160-200° C., and the blown film thickness is 0.04-0.06 mm.

[0171] The method of this embodiment is executed based on the above-mentioned component embodiments, and its principles and technical effects are similar, so they will not be repeated here.

[0172] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A low-carbon bio-based anti-counterfeiting packaging material, characterized in that: According to weight percentage, it includes the following components: Bio-based polyethylene 65% to 75%; Polylactic acid 10% to 15%; Dynamic molecular self-assembly unit 5% to 10%; Phase change material 8% to 12%; Optical control unit 0.1%~0.5%; Interface modifier 1% to 3%; Antioxidant 0.1%~0.2%; Antistatic agent 0.2%~0.3%.

2. A low-carbon bio-based anti-counterfeiting packaging material according to claim 1, characterized in that: The weight ratio of the bio-based polyethylene to the polylactic acid is 7:3 to 8:

2.

3. The low-carbon bio-based anti-counterfeiting packaging material according to claim 1, characterized in that: The dynamic molecular self-assembly unit is a cholesteric liquid crystal compound or a block copolymer liquid crystal polymer.

4. The low-carbon bio-based anti-counterfeiting packaging material according to claim 1, characterized in that: The phase change material is polyethylene glycol with a molecular weight of 4000 to 8000, and its phase change temperature range is 30 to 45°C.

5. The low-carbon bio-based anti-counterfeiting packaging material according to claim 1, characterized in that: The optical regulation unit is a ZnO quantum dot or an optical regulation unit quantum dot, and the particle size is 2-10 nm.

6. The low-carbon bio-based anti-counterfeiting packaging material according to claim 1, characterized in that: The interface modifier is maleic anhydride grafted polyethylene or a phosphate grafted agent.

7. The low-carbon bio-based anti-counterfeiting packaging material according to claim 1, characterized in that: The packaging material is a film made by a film blowing process, the film thickness is 0.04-0.06mm, and the surface flatness error is ±0.005mm.

8. A method for preparing a low-carbon bio-based anti-counterfeiting packaging material, according to the low-carbon bio-based anti-counterfeiting packaging material according to claims 1 to 7, characterized in that: The following steps are involved: S1, pre-treating the dynamic molecular self-assembly unit and the phase change material to form a uniform dispersed phase; S2, melt blending bio-based polyethylene and polylactic acid at a weight ratio of 7:3 to 8:2 at 160 to 180° C. to obtain a matrix material; S3, melt-blending the dispersed phase and the matrix material at 180-200° C., and adding an interface modifier to obtain a composite material; S4, blowing the composite material through a single screw extruder, the extrusion temperature is 160-200° C., and the film thickness is 0.04-0.06 mm; S5. An anti-counterfeiting mark is made on the surface of the film by using laser engraving technology, and a solution of an optical control unit is coated and then thermally cured to obtain an anti-counterfeiting packaging material.

9. The method for preparing a low-carbon bio-based anti-counterfeiting packaging material according to claim 8, characterized in that: The dynamic molecular self-assembly unit and the dispersed phase of the phase change material are prepared by ultrasonic dispersion technology, the ultrasonic power is 100-150W, and the processing time is 20-30min.

10. The method for preparing a low-carbon bio-based anti-counterfeiting packaging material according to claim 8, characterized in that: The film blowing cooling rate is controlled at 5-10°C / s, and the die head temperature is 190-210°C.